Bioinformatic Challenges Detecting Genetic Variation in Precision Medicine Programs - Field, Matt A. (Frontiers in Medicine, 2022)
Precision medicine programs to identify clinically relevant genetic variation have been revolutionized by access to increasingly affordable high-throughput sequencing (HTS) technologies. A decade of continual drops in per-base sequencing costs means it is now feasible to sequence an individual patient genome and interrogate all classes of genetic variation for less than $1000 USD. However, while advances in these technologies have greatly simplified the ability to obtain patient sequence information, the timely analysis and interpretation of genetic variation is limiting the full potential of large-scale precision medicine programs. This review will examine the challenges and potential solutions that exist in identifying predictive biomarkers in a patient and discuss the larger bioinformatic challenges likely to emerge in the future. It will detail how both software and hardware development are aiming to overcome issues in variant detection and variant interpretation. It will discuss the current state of the art in precision medicine for genetic disease and the challenges remaining for complex disease. Success across all disease types will require novel statistical models and software in order to ensure precision medicine programs realize their full potential now and into the future.